Rural diets under pressure: Food environments and their influence on food choice in South Asia - Chauhan, Alka; Scott, Samuel P.; Joe, William; Maharjan, Nanda Kumar; Menon, Purnima; Chakrabarti, Suman (2025)
The rapid South Asia rural transformation, driven by globalization and industrialization, has introduced a complex interaction between traditional and modern food systems. This study characterizes rural food environments in five districts across Bangladesh, India, and Nepal, focusing on how affordability, availability, accessibility, desirability, and convenience shape dietary choices and quality. Through extensive household and market surveys, we find rural diets characterized by low intake of healthy foods and moderate to high consumption of unhealthy options, influenced by a lack of affordability and the desirability and widespread availability of cheap ultra-processed products in rural markets. Snacking plays a significant role in shaping dietary patterns, promoting both dietary diversity and unhealthy food consumption. These findings provide essential insights for designing interventions tailored to rural food systems, supporting efforts to improve nutrition and health outcomes in rapidly changing markets.